Multi-Interfacial Confined Assembly of Colloidal Quantum Dots Quasisuperlattice Microcavities for High-Resolution Full-Color Microlaser Arrays - Li, Hui (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2024 Wiley‐VCH GmbH.